Code red : how progressives and moderates can unite to save our country - Dionne, E. J, Jr (St. Martin's Press, 2020)
"New York Times bestselling author and Washington Post columnist E. J. Dionne, Jr. sounds the alarm in Code Red, calling for an alliance between progressives and moderates to seize the moment and restore hope to America's future for the 2020 presidential election. Will progressives and moderates feud while America burns? Or will these natural allies take advantage of the greatest opportunity since the New Deal Era to strengthen American democracy, foster social justice, and turn back the threats of the Trump Era? The United States stands at a crossroads. Broad and principled opposition to Donald Trump's presidency has drawn millions of previously disengaged citizens to the public square and to the ballot boxes. This inspired and growing activism for social and political change hasn't been seen since the days of Franklin Roosevelt's New Deal policies and the Progressive and Civil Rights movements. But if progressives and moderates are unable-and unwilling-to overcome their differences, they could not only enable Trump to prevail again but also squander an occasion for launching a new era of reform. In Code Red, award-winning journalist E. J. Dionne, Jr., calls for a shared commitment to decency and a politics focused on freedom, fairness, and the future, encouraging progressives and moderates to explore common ground and expand the unity that brought about Democrat victories in the 2018 elections. He offers a unifying model for furthering progress with a Politics of Remedy, Dignity, and More: one that solves problems, resolve disputes, and moves forward; that sits at the heart of the demands for justice by both long-marginalized and recently-displaced groups; and that posits a positive future for Americans with more covered by health insurance, more with decent wages, more with good schools, more security from gun violence, more action to roll back climate change. Breaking through the partisan noise and cutting against conventional wisdom to provide a realistic look at political possibilities, Dionne offers a strategy for progressives and moderates to think more clearly and accept the responsibilities that history now imposes on them. Because at this point in our national story, change can't wait"--